Role of Wnt/β-catenin pathway in the nucleus accumbens in long-term cocaine-induced neuroplasticity: a possible novel target for addiction treatment - Cuesta, Santiago (2017)
Cocaine addiction is a chronic relapsing disorder characterized by the loss of control over drug-seeking and taking, and continued drug use regardless of adverse consequences. Despite years of research, effective treatments for psycho-stimulant addiction have not been identified. Persistent vulnerability to relapse arises from a number of long-lasting adaptations in the reward circuitry that mediate the enduring response to the drug. Recently, we reported that the activity of the canonical or Wnt/β-catenin pathway in the prefrontal cortex (PFC) is very important in the early stages of cocaine-induced neuroadaptations. In the present work, our main goal was to elucidate the relevance of this pathway in cocaine-induced long-term neuroadaptations that may underlie relapse. We found that a cocaine challenge, after a period of abstinence, induced an increase in the activity of the pathway which is revealed as an increase in the total and nuclear levels of β-catenin (final effector of the pathway) in the nucleus accumbens (NAcc), together with a decrease in the activity of glycogen synthase kinase 3β (GSK3β). Moreover, we found that the pharmacological modulation of the activity of the pathway has long-term effects on the cocaine-induced neuroplasticity at behavioral and molecular levels. All the results imply that changes in the Wnt/β-catenin pathway effectors are long-term neuroadaptations necessary for the behavioral response to cocaine. Even though more research is needed, the present results introduce the Wnt canonical pathway as a possible target to manage cocaine long-term neuroadaptations.